Expeditions through image jungles: The commercial use of image libraries in an online environment. Issue 1 (11th January 2016) - Göker, Ayse; Butterworth, Richard; MacFarlane, Andrew; Ahmed, Tanya S; Stumpf, Simone
Abstract : Purpose: – Searching for appropriate images as part of a work task is a non-trivial problem. Journalists and copywriters need to find images that are not only visually appropriate to accompany the documents they are creating, but are acceptably priced and licensed. The paper aims to discuss these issues. Design/methodology/approach: – A work-based study methodology and grounded theory are used to collect qualitative data from a variety of creative professionals including journalists. Findings: – The authors report the findings of a study to investigate image search, retrieval and use by creative professionals who routinely use images as part of their work in an online environment. The authors describe the commercial constraints that have an impact on the image users' behaviour that are not reported in other more academic and lab-based studies of image use (Westman, 2009). Practical implications: – The authors show that the commercial image retrieval systems are based on document retrieval systems, and that this is not the most appropriate approach in the journalism domain. Originality/value: – The authors describe the properties of an "information expedition"; the image seeking behaviour exhibited by journalists in an online environment, and contend that it is significantly different to existing image seeking models which represent other user types.